Spectrum of epilepsy in Neurocysticercosis - Kumar, Anoop; Singh, R.R; Verma, VK; Uraiya, Dharmendra; Tripathi, N. (International Journal of Medical Research and Review, 2016)
Introduction: Neurocysticercosis (NCC) is one of the most common parasitic cause of neurological disease in developing countries. NCC is the infestation of the central nervous system with the larvae of pork tapeworm, Taenia solium. It is endemic in South Asia, Africa, and Latin America. Due to increasing international travel and immigration, NCC is no more a health issue limited to the developing countries but also to the rest of world. Material and methods: A total of 70 patients of seizures presenting with ring enhancing lesion in CT scan of brain suggestive of neurocysticercosis, attending outpatient department or admitted in wards of Medicine Department of S.R.N. Hospital. A detailed seizure history as well as neurological examination was done according to the working proforma. Results: Maximum number of patients 34(48.57%) were presented with simple partial seizures with secondary generalization. Generalized tonic-clonic seizure was present in 22 patient (31.43%) patients. Simple partial seizure without secondary generalization was presented in 12 patients (17.14%). Two patients (2.86%) were presented with complex partial seizure. Conclusion: Neurocysticercosis is more common in young, rural population and in lower socioeconomic class. Vegetarians were significantly more affected than non-vegetarians which suggest other mode of transmission. By combining hygiene education and better sanitation, we will interrupt or reduce the cycle of direct person-to-person transmission. Thus, probably we will succeed to reduce the burden of disease from the society.